Examination of the Implementation of Gold Guarantee Financing from the Perspective of DSN-MUI Fatwa and Muamalah Fiqh - Sholeh Wafie; Aunur Rofiq; Khusnudin Khusnudin; Moch Mahsun (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
The purpose of this study is to assess the appropriateness of the gold pawn financing contract with the DSN-MUI fatwa and fiqh muamalah at the BMT UGT Nusantara Legung Branch. Data is gathered by observation, interviews, and recording as part of the qualitative research methodology, which also incorporates a field and literature approach. The findings demonstrated that a legally qualified applicant, gold collateral, and ujrah determination in line with the nominal financing are all necessary for the BMT UGT Nusantara Legung Branch to carry out the financing contract. The contracts utilised are qard and rahn, and in the event of default, gold collateral is sold without going through an auction. This implementation is generally adequate when considering fiqh muamalah and the DSN-MUI fatwa; nonetheless, it is important to highlight three key differences: 1. According to fiqh muamalah, the finance agreement employs qard and rahn, but the DSN-MUI fatwa has an extra ijarah agreement. 2. According to fiqh muamalah, the agreement and the amount of finance determine the gold storage fee; nevertheless, the DSN-MUI fatwa restricts the fee to actual expenditures. 3. According to fiqh muamalah, the sale of gold collateral without an auction is acceptable; nevertheless, the DSN-MUI fatwa mandates an auction procedure in the event that the rahin is unable to repay the loan. This study demonstrates that, despite being permitted under muamalah fiqh, three practices used in the BMT UGT Nusantara Legung Branch's financing contract with gold collateral are not compliant with the DSN-MUI fatwa.